(untitled) (e-Journal of Linguistics, 2023)
Nganjuk Regency, located in East Java, is known as an agricultural production area. In the past, rice was an expensive food commodity, leading the community to seek rice substitutes. One of the alternatives was the utilization of various traditional plant lexicons such as tales, gembili, uwi, garut, ganyong, gadung, suweg, and kentang ireng. The utilization of these plant lexicons by the Nganjuk community reflects their close connection with nature. This study aims to provide a descriptive and qualitative depiction of the usage of rice substitute lexicons in the culture of Nganjuk society. Research data was collected through interviews and observations. Interviews were conducted to understand the functions and meanings of using rice substitute lexicons in Nganjuk society.The findings of this study provide a deep understanding of the diversity of traditional plant lexicons used as rice substitutes in Nganjuk Regency. It was found that mbote / kimpul, gembili, uwi, garut, ganyong, gadung, suweg, and kentang ireng are plants that have long been known and utilized by the Nganjuk community as valuable sources of carbohydrates. The utilization of these lexicons is not limited to the past but continues to the present.The community’s connection with nature is reflected in their knowledge of these plant lexicons. The Nganjuk community has a profound understanding of the benefits and uses of each plant. They appreciate biodiversity and integrate this knowledge into their daily lives. However, this research also reveals a shift occurring in the younger generation. In the modern era, with abundant availability and the dominance of rice consumption, these traditional plant lexicons tend to be forgotten and less known by the current generation. This highlights the need to preserve the knowledge and traditional practices related to plant lexicons as rice substitutes. In this context, this research makes a significant contribution to enriching the understanding of cultural wealth and traditional values related to food in Nganjuk Regency. These findings can serve as a basis for developing efforts in preservation, education, and promotion of the use of traditional plant lexicons as healthy and sustainable rice substitutes.